A Descriptive Study On Teaching English For YoungLearner At Sd 1 Posong In 2013/2014 Academic Year - Sulistyawikan, Febrina Anggri, Aryati Prasetyarini, S.Pd, M.Pd, Mauly Halwat Hikmat, Ph. D (2014)
In general this study aims (1) to describe the implementation of teaching English for young learner of the fifth grade at SD 1 Posong Batang and specially to (a) the teaching techniques, (b) teaching procedure and (c) teaching media, and (2) to identify whether the teaching is in line with the principle of TEYL or not. The type of this research is descriptive qualitative research. The researcher collects the data by observing the teaching learning English for young learner and conducting an interview. The data are field note and interview script. The methods of collecting data are observation, interview, and document. The techniques for analyzing data include data reduction, data display, and conclusion and verification. The results of the research show that the teaching learning process runs well enough. In teaching English for the fifth grade the teacher used (a) translation, picture and draw the sketch, example - illustration clues, quiz, and memorize vocabulary as a technique. (b) the procedure are opening, explanation, and closing. (c) the media used by teacher in teaching English are blackboard, chalk, and any concrete object in the class surrounding. And the teaching learning process at SD 1 Posong in 2013-2014 academic year is in line with principle of TEYL.